2018
DOI: 10.1002/smll.201704414
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Graphene–GeSn Quantum Well Heterostructure SWIR Light Source

Abstract: The problem of light source always prevents silicon-based photonics from achieving a final integration. Although some optical pump lasers have been reported in recent years, an electrical pumping laser is considered as the ultimate solution. To fabricate a Si-based laser, there are some crucial obstacles that need to be solved such as difficulties in material epitaxy, light absorption by metal electrodes, and compatibility with the existing complementary metal-oxide-semiconductor transistor process. Here, a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Generally, a strain sensor made of a 1D material always exhibits a large working range but a poor sensitivity, since 1D materials with a high aspect ratio can maintain good interconnection while manifesting inconspicuous resistance changes under an extended strain range . Conversely, strain sensors based on 2D materials demonstrate good sensitivity but suffer from low stretchability and stability, which may be related with the low aspect ratio of 2D materials . Recent research has suggested that the strong interaction (i.e., hydrogen bonds or van der Waals forces) between adjacent sheets may play a critical role in narrowing the working range, which obstructs the effective slippage between the sheets so that the 2D materials are inclined to rapidly split into scales and cut off the conductive pathways during the tensile process.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a strain sensor made of a 1D material always exhibits a large working range but a poor sensitivity, since 1D materials with a high aspect ratio can maintain good interconnection while manifesting inconspicuous resistance changes under an extended strain range . Conversely, strain sensors based on 2D materials demonstrate good sensitivity but suffer from low stretchability and stability, which may be related with the low aspect ratio of 2D materials . Recent research has suggested that the strong interaction (i.e., hydrogen bonds or van der Waals forces) between adjacent sheets may play a critical role in narrowing the working range, which obstructs the effective slippage between the sheets so that the 2D materials are inclined to rapidly split into scales and cut off the conductive pathways during the tensile process.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also observed that the In 2 O 3 film modified by Au@C nanoparticles has better gas sensing properties than that modified by Au nanoparticles, indicating that the ultrathin carbon layer plays an important role on the gas sensing process. This is due to the unique electronic properties of carbon materials, such as high carrier mobility and the high sensitivity to the changes of resistance [ 38 , 39 , 40 ]. The ultrathin carbon layer can rapidly transform the electric carriers generated from the sensing process, and local p-n heterojunctions are created between carbon layer and In 2 O 3 film, in which the carbon layer plays a role as a p-type semiconductor [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the low (1%) equilibrium solubility of Sn in Ge [9,10] and the large lattice mismatch (~15%) between Ge and α-Sn introduce enormous challenges for the realization of defect-free GeSn alloy with even a few atomic % of substitutional Sn. The use of non-equilibrium growth techniques such as low-temperature molecular beam epitaxy (MBE) [11][12][13][14][15], chemical vapor deposition (CVD) [16][17][18][19][20], and solid-phase epitaxy [21,22] is in great need.…”
Section: Introductionmentioning
confidence: 99%